Green sustainable process for chemical and environmental engineering and science : solid-state energy storage : a path to environmental sustainability - Smirnova, Alevtina; Numan-Al-Mobin, Abu; Inamuddin, 1980- (Elsevier, 2023)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Solid-State Energy Storage - A Path to Environmental Sustainability offers an in-depth analysis of the synthesis methods, manufacturing techniques and underlying mechanisms of ionic and electronic-ion transport in various single phase and multi-phase components for electric power storage, such as lithium and sodium ion batteries, sulfur batteries, and lithium-metal electrochemical systems. Though solid-state batteries are not yet available on the market, many large corporations and small companies pursue the goal of implementing this technology for numerous applications and its transfer to other markets.